2015
DOI: 10.1590/s1806-37132015000000025
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-induced pulmonary changes: HRCT findings

Abstract: Objective: To evaluate HRCT scans of the chest in 22 patients with cocaine-induced pulmonary disease. Methods: We included patients between 19 and 52 years of age. The HRCT scans were evaluated by two radiologists independently, discordant results being resolved by consensus. The inclusion criterion was an HRCT scan showing abnormalities that were temporally related to cocaine use, with no other apparent causal factors. Results: In 8 patients (36.4%), the clinical and tomographic findings were consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
0
14
0
2
Order By: Relevance
“…Clinical presentation and radiological findings are varied and highly nonspecific. 4 PFBG is a rare condition, and its true incidence is unknown. It is commonly encountered secondary to intravenous injection of pulverized pharmaceutical tablets containing insoluble binders, such as talc, cellulose, starch, and other street adulterants.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical presentation and radiological findings are varied and highly nonspecific. 4 PFBG is a rare condition, and its true incidence is unknown. It is commonly encountered secondary to intravenous injection of pulverized pharmaceutical tablets containing insoluble binders, such as talc, cellulose, starch, and other street adulterants.…”
Section: Discussionmentioning
confidence: 99%
“…It is a widely abused substance, because of its strong sympathomimetic and central nervous system stimulant effects, which are due to its capacity to interfere with the reuptake of catecholamines and serotonin. HRCT patterns associated with cocaine toxicity include GGO (reported in 100% of the cases) ( Figure 9); consolidations (50%); the halo sign (25%); as well as smooth septal thickening, paraseptal emphysema, centrilobular nodules, and the tree-in-bud pattern ( Figure 10) [48]; however, as many cocaine abusers are also marijuana or tobacco smokers, it is difficult to determine which alterations are specifically caused by cocaine [49]. Alterations provoked by cocaine can be divided in acute or chronic.…”
Section: Psychoactive Drugmentioning
confidence: 99%
“…Postero-anterior and lateral CXR and CT have definitely ruled out alternative causes of PM such as thoracic trauma, oesophageal rupture, and pulmonary infection. CXR and CT are important tools to investigate PM due to tracheobronchial tree laceration [10]. The analysis of cases of 104 patients affected by spontaneous PM showed that the main predisposing factors are young age, male sex, age less than 30 years, asthma, chronic bronchitis, and drug use [11].…”
Section: Discussionmentioning
confidence: 99%